The Peruvian Society of Obstetrics and Gynecology and Family Planning - Ciudad Reynaud, Antonio (2017)
The Peruvian Society of Obstetrics and Gynecology (SPOG) in its 70 years of institutional life has contributed to the analysis and implementation of Family Planning in Peru. The SPOG has reviewed and reflected on family planning through its institutional Journal, in the Peruvian and International Congresses, in Conferences, in updating Scientific Activities and in Courses for OB/GYN residents organized throughout its 70 years of institutional life. In the SPOG Journal, the most discussed topics have been the need to have a public policy of family planning as a fundamental part of Reproductive Health policy, the efficacy of different contraceptive methods and their impact and existing relationship with other major health problems for women: abortion, infections and maternal mortality.